Shear Strengthening of Reinforced Concrete Beams Using GFRP - Liew, Yu Xuan; Norliana, Bakar; Lim, Kar Sing; Doh, Shu Ing; Putra Jaya, Ramadhansyah; Chin, Siew Choo (Bentham Open, 2023)
Background: Glass fibre-reinforced polymer (GFRP) is often used as external strengthening material due to its unique benefits. However, the effectiveness of the strengthening configuration, which uses GFRP in different orientations, still has a lot of uncertainties. Objective: This research work aims to study the shear strengthening of reinforced concrete beams using GFRP. Methods: The mechanical properties of the GFRP were investigated, including tensile and flexural tests. Two layers of GFRP were bonded together using epoxy and a hardener of 2:1. The GFRP was then cut according to size for tensile and flexural tests. Five samples were prepared for tensile and flexural tests, respectively. In terms of beam strengthening, a total of four beams were considered for four-point bending tests, whereby two were used as control beams and the remaining two were for strengthening purposes. A 45º strengthening configuration was adopted for the shear strengthening. Results: Results showed that GFRP possessed the highest tensile stress, which was achieved in the range of 208.85 MPa – 319.22 MPa, while the highest flexural stress was achieved in the range of 506.16 MPa – 592.49 MPa. The results showed that shear strengthening at 45º with GFRP achieved an ultimate load of 136.38 kN, which was higher than the control beam's load of 133 kN. This indicates that GFRP managed to regain the beam capacity, which is 2.5% higher than the control beam. Conclusion: This proves that GFRP can be used as an alternative strengthening material other than carbon fibre-reinforced polymer (CFRP).